The Impact Of The Mini-games Exercises During A Training Programme In Developing The Skills Of Passing, Receiving And Controlling The Ball For Football Players Under 17 Years. - Hadjab Issam . (sports creativity, 2025)
Abstract: The study aimed at identifying the extent of the contribution of the training program that is based on mini-games in developing the basic skills among under 17 years football players. To evaluate the extent of the effectiveness, the researcher conducted a study at the level of the regional championship of the State of Annaba on a sample of 20 players from Khadraoui Ahmed Team (experimental sample) and the Team of Sedrata Union with other 20 players (referential sample). They were intentionally selected for the research. In this study the researcher applied the experimental method through making a pre-test followed by the application of the training program that was designed by the researcher and then ended with a post test. By analysing the results, the researcher concluded that the training program based on mini-games contributed positively in the development of the studied basic skills. .